Actually super - Alsaid, Adi (Knopf Books for Young Readers, 2023)
"Isabel is having an existential crisis. She's three years into high school, and everything she's learned has only shaken her faith in humanity. Late one night, she finds herself drawn to a niche corner of the internet--a forum whose members believe firmly in one thing: that there are indeed people out in the world quietly performing impossible acts of heroism. You might even call them supers. No, not in the comic book sense--these are real people, just like each of us, but who happen to have a power or two. If Isabel can find them, she reasons, she might be able to prove to herself that humanity is more good than bad. So, the day she turns 18, she sets off on a journey that will take her from Japan to Australia, and from Argentina to Mexico, with many stops along the way. She longs to prove one--just one--super exists to restore her hope for the future. Will she find what she's looking for? And how will she know when-if-she does?" --